(2x-1)(2x+1)=4x*4x+4x+2

Simple and best practice solution for (2x-1)(2x+1)=4x*4x+4x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-1)(2x+1)=4x*4x+4x+2 equation:



(2x-1)(2x+1)=4x*4x+4x+2
We move all terms to the left:
(2x-1)(2x+1)-(4x*4x+4x+2)=0
We add all the numbers together, and all the variables
(2x-1)(2x+1)-(4x+4x*4x+2)=0
We use the square of the difference formula
4x^2-(4x+4x*4x+2)-1=0
We get rid of parentheses
4x^2-4x-4x*4x-2-1=0
We add all the numbers together, and all the variables
4x^2-4x-4x*4x-3=0
Wy multiply elements
4x^2-16x^2-4x-3=0
We add all the numbers together, and all the variables
-12x^2-4x-3=0
a = -12; b = -4; c = -3;
Δ = b2-4ac
Δ = -42-4·(-12)·(-3)
Δ = -128
Delta is less than zero, so there is no solution for the equation

See similar equations:

| -35=4u+1 | | 8.3d+16.47=-9.5d-7.26+6.5d | | Un=3n+1 | | 5=-6+5x | | 3x=5+10 | | 4n+2+8n-10=180 | | (2x-1)(2x+1)=4x*4x-1 | | |-x+9|=-21 | | 3(x−9)+6x=9x−27 | | |-x+9|=21 | | -5r-3=-3(1-r) | | 17+3x+5=5x+2 | | 3s=-1 | | 2.8(x-2.5)=14 | | 2-q/3=7 | | 2m+4(m−3)=7m−42m+4(m−3)=7m−4 | | -28x+20x=4(-9-3x) | | (2x-1)(2x+1)=4x+1 | | -39+8k=-5(3-4k) | | 2(z+5)+4=4 | | 2n-10n=2 | | 4x-8=4x+(-4) | | x+65.35=x-127.75 | | 3p/14=7/6 | | 5x+13-3x+33=70 | | 4^2+4w+1=75 | | -5-n=-4(n-4)+3 | | 11-3n=7(n-7) | | 6)11-3n=7(n-7) | | -3s^2-17s+56=0 | | x*25=5000-x | | -190=-5(8a+6) |

Equations solver categories